PENYUSUNAN ROAD MAP REFORMASI BIROKRASI PEMERINTAH KOTA PEKANBARU TAHUN 2012-2017 - Pratiwi, Cintia; ', Erman M (Nakhoda: Jurnal Ilmu Pemerintahan, 2014)
This study , entitled " Preparation of Road Map Pekanbaru City Government ReformsYear 2012 - 2017 " This research is motivated by the Regulation of the Minister ofAdministrative Reform and Bureaucratic Reform No. 96 Year 2013 on the Establishment ofRegional Pilot Project Reforms supported by the Local Government and Regulation of theMinister of Administrative Reform state No. 37 Year 2013 on Guidelines for Preparation of RoadMap for local Government reforms , which in the regulation states that the Government ofPekanbaru City designated as one of the Bureaucratic Reform Pilot Project , and each regionPilot Project including Pekanbaru required to prepare Road Map reforms for term the next 5years . Issues contained in this paper are still poor face Pekanbaru city government bureaucracy, lack of Quick Wins program in the preparation of the Road Map , lack of socialization RoadMap bureaucratic reform and not the establishment of a special regional regulations governingthe Road Map Pekanbaru City Government Reforms of 2012 -2017 . The method used in thisstudy is a qualitative method that describes the descriptive data . Data collection techniquesused were interviews , observation and document tracking . While the source of the data used isprimary data obtained from the study site and supported by secondary data .Based on the results of research conducted there is some obstacle in the preparation ofthe Road Map is one of them happens tug of interest, lack of a strong commitment to thestructures involved in the implementation of bureaucratic reform , there is a bottleneck in termsof the budget in the absence of specific regulations governing the area of the Road Map reformbureaucracy , having compiled a lack of socialization both internally and universal , the lack ofquick wins in the Road Map , so that the step or action plan contained in the Road Map arerepeat or hamier most of it is still the same as the program that has been done previouslyPekanbaru city government .Keywords :reform bureaucracy , Road Map